Do Class Size Reductions Protect Students from Infectious Disease? Lessons for COVID-19 Policy from Flu Epidemic in Tokyo Metropolitan Area - Masato Oikawa; Ryuichi Tanaka; Shun-ichiro Bessho; Haruko Noguchi (Institute of Labor Economics (IZA), 2020)
We evaluate the causal effect of class size (i.e., number of students in a classroom) on incidence of class closure due to flu epidemic in 2015, 2016, and 2017, applying an instrumental variable method with the Maimonides rule to administrative data of public primary and middle school students in one of the largest municipalities within the City of Tokyo Metropolitan Area. Given the classroom area of 63m2 set by regulation in Japan, class size reduction improves social distancing among students in a classroom. We find that class size reduction is effective to reduce class closure due to flu: one unit reduction of class size decreases class closure by about 5%; and forming small classes with 27 students at most, satisfying the social distancing of 1.5 m recommended to prevent droplet infection including influenza and COVID-19, reduces class closure by about 90%. In addition, we find that the older are students, the larger are the effects of class size reduction. Our findings provide supportive evidence for the effectiveness of social distancing policy in primary and middle schools to protect students from droplet infectious disease including COVID-19.
Keywords: I18; I21; I28; 330; class size; class closure; students health; influenza(flu) epidemic; lesson for COVID-19; COVID-19